(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
Tuberculous spondylitis, also known as hospital-acquired tuberculosis, is a rare but serious manifestation of tuberculosis infection affecting the spine and spinal cord. This article reviews the epidemiology, pathophysiology, clinical presentation, diagnosis, and treatment options for tuberculous spondylitis.